2022
DOI: 10.1175/jas-d-20-0275.1
|View full text |Cite
|
Sign up to set email alerts
|

New Empirical Formulation for the Sublimational Breakup of Graupel and Dendritic Snow

Abstract: Ice fragments are generated by sublimation of ice particles in subsaturated conditions in natural clouds. Conceivably, such sublimational breakup would be expected to cause ice multiplication in natural clouds. Any fragment that survives will grow to become ice precipitation that may sublimate and fragment further.As a first step towards assessing this overlooked process, a formulation is proposed for the number of ice fragments from sublimation of ice particles for an atmospheric model. This is done by amalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…questioned the efficacy of sublimation breakup as a SIP mechanism, stating that "it remains unclear whether small fragments formed in the subsaturated environment can re-enter supersaturated cloud and act as SIP particles." While their argument limits a certain (potentially large) fraction of such events, Deshmukh et al (2022) recently concluded that ice fragments formed via this sublimation-induced mechanism could nevertheless have lifetimes greater than 1 min in ice-subsaturated conditions. In their comparison of model simulations with in-situ measurements from an Alpine station, Georgakaki et al ( 2022) deduced that the sublimation SILBER 10.1029/2022JD038202…”
Section: Discussionmentioning
confidence: 99%
“…questioned the efficacy of sublimation breakup as a SIP mechanism, stating that "it remains unclear whether small fragments formed in the subsaturated environment can re-enter supersaturated cloud and act as SIP particles." While their argument limits a certain (potentially large) fraction of such events, Deshmukh et al (2022) recently concluded that ice fragments formed via this sublimation-induced mechanism could nevertheless have lifetimes greater than 1 min in ice-subsaturated conditions. In their comparison of model simulations with in-situ measurements from an Alpine station, Georgakaki et al ( 2022) deduced that the sublimation SILBER 10.1029/2022JD038202…”
Section: Discussionmentioning
confidence: 99%
“…Based on the argument of Korolev and Leisner (2020) and that small ice fragments in a subsaturated cloud environment are more likely to fully sublimate before they return to a cloud zone supersaturated with respect to ice, it might be unlikely that this mechanism is important in atmospheric clouds. In contrast, Deshmukh et al (2022) could theoretically derive a significant contribution of SIP due to sublimation taken also graupel into account. It is conceivable that the mechanism may be important in regions near the cloud edge where entrainment of dry air occurs, as discussed earlier by Bacon et al (1998).…”
Section: Rime-splinteringmentioning
confidence: 95%
“…The production rate depends on the density and shape of ice particles, as well as the collision kinetic energy. Deshmukh et al (2022) proposed a formulation for the number of ice splinters generated during ice sublimation based on laboratory observations. The relative humidity on the ice and the preliminary size of the mother ice particles both govern the number of ice splinters.…”
Section: Model Setup and Design Of Numerical Experimentsmentioning
confidence: 99%
“…However, rime splintering is not the only SIP process that can influence the charge structure of thunderstorms. Secondary ice can be produced through various processes, such as the shattering of freezing drops, ice-ice collisional breakup, and sublimational breakup of ice (Lauber et al, 2018;Phillips et al, 2018;Korolev and Leisner, 2020;Deshmukh et al, 2022). Recently, Phillips and Patade (2022) showed that the ice-ice collisional breakup may significantly alter the charge structure of summertime thunderstorms using a high-resolution cloud model.…”
Section: Introductionmentioning
confidence: 99%